Chondrodysplasia with multiple dislocations: comprehensive study of a series of 30 cases - ELÇİOĞLU, HURİYE NURSEL (WILEY, 2017)
The group of chondrodysplasia with multiple dislocations includes several entities, characterized by short stature, dislocation of large joints, hand and/or vertebral anomalies. Other features, such as epiphyseal or metaphyseal changes, cleft palate, intellectual disability are also often part of the phenotype. In addition, several conditions with overlapping features are related to this group and broaden the spectrum. The majority of these disorders have been linked to pathogenic variants in genes encoding proteins implicated in the synthesis or sulfation of proteoglycans (PG). In a series of 30 patients with multiple dislocations, we have performed exome sequencing and subsequent targeted analysis of 15 genes, implicated in chondrodysplasia with multiple dislocations, and related conditions. We have identified causative pathogenic variants in 60% of patients (18/30); when a clinical diagnosis was suspected, this was molecularly confirmed in 53% of cases. Forty percent of patients remain without molecular etiology. Pathogenic variants in genes implicated in PG synthesis are of major importance in chondrodysplasia with multiple dislocations and related conditions. The combination of hand features, growth failure severity, radiological aspects of long bones and of vertebrae allowed discrimination among the different conditions. We propose key diagnostic clues to the clinician.
Keywords: chondrodysplasia; genotype-phenotype correlation; joint dislocations; proteoglycans; targeted NGS; SPONDYLOEPIMETAPHYSEAL DYSPLASIA; DESBUQUOIS DYSPLASIA; PHENOTYPIC SPECTRUM; LARSEN-SYNDROME; JOINT LAXITY; MUTATIONS; GENE; DEFICIENCY; SKELETAL; ENZYME